2014
DOI: 10.1371/journal.pone.0109654
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Comparability of Controlled Human Plasmodium falciparum Infection by Mosquito Bite in Malaria-Naïve Subjects at a New Facility for Sporozoite Challenge

Abstract: BackgroundControlled human malaria infection (CHMI) studies which recapitulate mosquito-borne infection are a critical tool to identify protective vaccine and drug candidates for advancement to field trials. In partnership with the Walter Reed Army Institute of Research, the CHMI model was established at the Seattle Biomedical Research Institute's Malaria Clinical Trials Center (MCTC). Activities and reagents at both centers were aligned to ensure comparability and continued safety of the model. To demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…The current analysis shows that this has made it possible to lower the treatment threshold much further. Likewise, other CHMI study centres have also repeatedly shown that qPCR first becomes positive 2–4 days before thick blood smear when both are determined [ 18 21 ]. Similarly, studies assessing blood stage drugs or vaccines have already begun to use qPCR as a primary outcome, and have confirmed its sensitivity and specificity [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…The current analysis shows that this has made it possible to lower the treatment threshold much further. Likewise, other CHMI study centres have also repeatedly shown that qPCR first becomes positive 2–4 days before thick blood smear when both are determined [ 18 21 ]. Similarly, studies assessing blood stage drugs or vaccines have already begun to use qPCR as a primary outcome, and have confirmed its sensitivity and specificity [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…Again, empirically, this translates into fully protective doses in murine models with oral administration at <10 mg/kg. Activity can be confirmed in CHMI sporozoite challenge studies [6062], and this will help put more objective criteria on TCP-4 over the coming years.…”
Section: Tcp-4: Targeting Hepatic Schizontsmentioning
confidence: 97%
“…The insights into the development of new medicines for chemoprotection over the last 4 years in this area can be summarized as follows.Confirmation of the activity in humans for activity against hepatic schizonts or newly emerging asexual erythrocytes can now be tested in controlled human malaria infection (CHMI) volunteer studies using either injected cryopreserved sporozoites [60, 61] or infectious mosquitoes [62]. Currently these models involve infection of non-immune volunteers who live in non-endemic regions, and so it will be important to extend this work to include studies of the impact on the immune response, and in an expanded genetic background.…”
Section: Chemoprotectionmentioning
confidence: 99%
“…In contrast to other pathogens, such as HIV and Mycobacterium tuberculosis , malaria vaccine efficacy can be tested using CHMIs. Although several centers have the technical expertise and logistics in place to run these trials [5760], anti-malaria chemotherapy is required as soon as parasite are detected in the blood. Thus, CHMIs are unsuitable to characterize the dynamics of the infection, which is needed to understand immune responses resulting in the control and elimination of the parasite and associated disease.…”
Section: The Path Forwardmentioning
confidence: 99%